Nano twin crystal oxygen-containing titanium alloy based on additive manufacturing technology and preparation method of nano twin crystal oxygen-containing titanium alloy

By adding TiO2 to the titanium alloy powder and optimizing additive manufacturing parameters, the problem of plastic loss when the strength of titanium alloy is increased in the prior art is solved, and high strength and toughness and low-cost titanium alloy preparation is achieved, and uniform mechanical properties are achieved.

CN119733848APending Publication Date: 2025-04-01XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510172018.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The prior art usually sacrifices its plasticity in the process of increasing the strength of titanium alloys, and it is difficult to effectively control the oxygen content in additive manufacturing to achieve high strength and low cost titanium alloys.

Method used

By adding TiO2 to the titanium alloy powder, the oxygen content in the mixed powder is adjusted to 0.1% to 0.5%, and the printing parameters of additive manufacturing technology, such as laser power, scanning speed and volume energy density, are optimized to achieve more oxygen solution and high strength and toughness.

Benefits of technology

It is realized that high strength, toughness and low cost titanium alloys are prepared without strict control of the powder oxygen content, and the material has the same mechanical properties at different construction heights and has a small ductility loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733848A_ABST
    Figure CN119733848A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of titanium alloy additive manufacturing, in particular to a nano twin crystal oxygen-containing titanium alloy based on an additive manufacturing technology and a preparation method thereof.The nano twin crystal oxygen-containing titanium alloy based on the additive manufacturing technology is characterized in that titanium alloy powder and TiO2 powder are mixed to obtain mixed powder, and the mass percent of oxygen in the mixed powder is 0.1 wt.%-0.5 wt.%; the mixed powder is subjected to laser printing, and the titanium alloy based on the additive manufacturing technology is obtained; wherein the printing parameters are as follows: the laser power is 150W to 375W, the scanning speed is 430mm / s to 1500mm / s, the scanning interval is 80mu m to 120mu m, and the volume energy density is 35J / mm < 3 > to 78J / mm < 3 >. The problem that in the prior art, the strength of the titanium alloy is generally improved at the cost of sacrifice plasticity is solved, the oxygen content of powder does not need to be strictly controlled, and the alloy is high in toughness and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of titanium alloy additive manufacturing, and in particular to a nano-twinned oxygen-containing titanium alloy based on additive manufacturing technology and a preparation method thereof. Background Art

[0002] Titanium and its alloys are increasingly used in biomedical, aerospace and marine applications due to their excellent properties, including high biocompatibility, high strength, appropriate Young's modulus and excellent corrosion resistance. In particular, TC4 (Ti6Al4V) alloy is widely used due to its advantages of light weight, high strength, corrosion resistance, high temperature resistance, excellent biocompatibility and high fracture toughness.

[0003] Oxygen is one of the α-phase stabilizer elements of titanium alloys. In composition design, oxygen has received extensive attention due to its excellent nucleation ability and strengthening effect. Titanium alloys are very sensitive to oxygen content. Micro-oxygen content (0.3wt.%~0.5wt.%) can significantly improve material strength, but as the oxygen content increases, ductility decreases sharply, accompanied by a transition from ductile fracture to brittle fracture. Therefore, interstitial oxygen has a strong influence on the microstructural characteristics and mechanical properties of titanium and titanium alloys.

[0004] Previous studies have shown that adding oxygen to titanium alloys can improve the strength, elastic modulus and hardness of titanium alloys, and significantly reduce the ductility of titanium alloys. Therefore, the strengthening effect of interstitial oxygen is limited. In order to ensure the mechanical properties of the sample, the oxygen content of the titanium alloy needs to be strictly controlled (≤0.2wt.%). Oxygen atoms tend to occupy the octahedral gaps of the α-Ti lattice, resulting in the expansion of the lattice. The increase in oxygen content will cause the lattice parameters of the α phase in the alloy to change, the hardness to increase, thereby improving the strength of the material, but at the same time reducing the plasticity and impact toughness of the material. Reducing the oxygen content can significantly improve the crack propagation resistance and impact resistance of the material. This is mainly because at low oxygen content, the dislocation activation and subgrain boundary formation inside the alloy help release internal stress and improve the plastic deformation coordination of the two phases. However, the increase in oxygen content is inevitable during the preparation, storage, and printing of powders. If the oxygen content is strictly controlled, the manufacturing cost will be greatly increased.

[0005] Titanium alloys prepared by traditional methods require a series of post-processing such as rolling or annealing to produce twins that are beneficial to the comprehensive performance of the material. However, due to the unique thermal cycle and rapid solidification of additive manufacturing, a high density of screw dislocations are formed inside the material, which promotes the nucleation of nanotwin precipitates.

[0006] The directional temperature gradient and rapid cooling rate inherent in the additive manufacturing process prevent nucleation before the solidification front and induce the formation of epitaxial columnar grains with preferential orientation along the build direction (BD), resulting in anisotropy of texture and mechanical properties. Currently, two methods are commonly used in the additive manufacturing process to refine the microstructure without post-processing. One method is to optimize the processing parameters of additive manufacturing to achieve lower temperature gradients and higher solidification rates, thereby inducing a large amount of undercooling to adjust the microstructure. However, this method has limited effects on the epitaxial growth-derived microstructure and columnar morphology. Another method is to increase the effective nucleation sites by adding foreign elements or particles. In contrast, additive manufacturing with shorter melting and solidification windows can allow quasi-stable compounds to survive during solidification and act as a heterogeneous matrix, which is more suitable for additive manufacturing processes. The oxygen element has attracted widespread attention in traditional manufacturing due to its excellent nucleation ability and strengthening ability.

[0007] In additive manufacturing technology, samples with different oxygen contents are generally constructed by adding TiO2 to the original powder. TiO2 with too large a particle size will be unevenly distributed during mixing, while TiO2 with too small a particle size is prone to agglomeration, both of which will affect the mechanical properties of the material. Liao et al. found that a new FCC phase will appear in the oxygenated TC4 prepared by additive manufacturing (by adding TiO2 with a particle size of less than 5μm). They found that the volume fraction of the FCC phase increased monotonically from 0.0vol.% in the top layer to 6.6vol.% in the bottom layer, and the yield strength, tensile strength and elongation increased by 128MPa, 69MPa and 1.1%, respectively.

[0008] In summary, how to prepare a titanium alloy that can accommodate more oxygen, has a synergistic effect of strength and toughness, and has low cost and no difference in mechanical properties at different build heights has become a current problem. Summary of the invention

[0009] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a titanium alloy based on additive manufacturing technology and a preparation method thereof, so as to solve the problem that the prior art usually improves the strength of titanium alloys at the expense of plasticity. Through the rapid cooling of additive manufacturing technology, a finer grain size can be achieved to accommodate more oxygen. At the same time, the process parameters can be adjusted to achieve a low-cost titanium alloy that does not require strict control of the oxygen content of the powder and has high strength and toughness.

[0010] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0011] A method for preparing a titanium alloy based on additive manufacturing technology comprises the following steps:

[0012] Titanium alloy powder and TiO2 powder are mixed under vacuum conditions to obtain mixed powder, wherein the mass percentage of oxygen in the mixed powder is 0.1% to 0.5%.

[0013] The mixed powder is laser printed to obtain a titanium alloy based on additive manufacturing technology.

[0014] The printing parameters are: laser power: 150W~375W, scanning speed: 430mm / s~1500mm / s, scanning spacing: 80μm~120μm, volume energy density: 35J / mm 3 ~78J / mm 3 .

[0015] The present invention is based on the prior art that usually sacrifices plasticity to improve the strength of titanium alloys. By adding TiO2 to the titanium alloy powder, the mass percentage of oxygen in the mixed powder is 0.1-0.5. At the same time, the printing parameters of the additive manufacturing technology are adjusted as follows: laser power: 150W-375W, scanning speed: 430mm / s-1500mm / s, scanning spacing: 80μm-120μm, volume energy density: 35J / mm 3 ~78J / mm 3 The present invention achieves more oxygen solid solution through additive manufacturing technology and adjustment of process parameters, because interstitial oxygen elements can significantly strengthen titanium alloys and provide a large amount of strength contribution to titanium alloys, but as the oxygen content increases, the ductility of titanium alloys will drop sharply. Therefore, by adjusting the process parameters, the titanium alloy can accommodate more oxygen, achieve higher oxygen solid solution strengthening, and at the same time the ductility of the material will not be lost too much, ensuring that the oxygen content in the titanium alloy powder is increased, and the introduction of oxygen does not produce FCC phase, so that the material has no difference in mechanical properties at different build heights, and at the same time the mechanical properties of the alloy will not drop significantly, thereby achieving the preparation of high-strength and tough titanium alloys at a lower cost.

[0016] In a preferred embodiment of the present invention, the printing parameters are: laser power: 175W, scanning speed: 720mm / s-740mm / s, scanning spacing: 80μm, volume energy density: 43J / mm 3 ~51J / mm 3 .

[0017] In a preferred embodiment of the present invention, the particle size of the titanium alloy powder is 15μm to 53μm, and the particle size of the TiO2 powder is 200nm to 300nm. The present invention mixes the titanium alloy powder and the TiO2 powder in a proportion in an argon-filled glove box (the oxygen content inside the glove box is less than 0.1%), and limits the particle size of the TiO2 powder to 200nm to 300nm. The mixed powder is not easy to agglomerate, and TiO2 is evenly distributed in the mixed powder.

[0018] In a preferred embodiment of the present invention, the printing layer thickness is 55 μm to 65 μm.

[0019] In a preferred embodiment of the present invention, the printing path is a unidirectional scan with an inter-layer rotation of 67°.

[0020] In a preferred embodiment of the present invention, the titanium alloy powder comprises, by mass percentage, Al: 5.5% to 7%, V: 3.5% to 5%, C: <0.1%, Fe: <0.1%, O: <0.1%, N: <0.1%, and Ti as the remainder, totaling 100%.

[0021] In a preferred embodiment of the present invention, the substrate is preheated before printing, and the preheating temperature is 190°C to 210°C.

[0022] Another object of the present invention is to provide a titanium alloy based on additive manufacturing technology obtained by any of the preparation methods described above.

[0023] In a preferred embodiment of the present invention, the mass percentage of oxygen in the titanium alloy is 0.1% to 0.5%, the yield strength is 810MPa to 1300MPa, the tensile strength is 905MPa to 1500MPa, and the elongation is 4.0% to 11.5%.

[0024] In a preferred embodiment of the present invention, the microstructure of the titanium alloy is nano twins.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. Based on the prior art, the strength of titanium alloy is usually improved at the expense of plasticity. TiO2 is added to the titanium alloy powder so that the mass percentage of oxygen in the mixed powder is 0.1-0.5. At the same time, the printing parameters of the additive manufacturing technology are adjusted as follows: laser power: 150W-375W, scanning speed: 430mm / s-1500mm / s, scanning spacing: 80μm-120μm, volume energy density: 35J / mm 3 ~78J / mm 3 The present invention achieves more oxygen solid solution through additive manufacturing technology and adjustment of process parameters, because interstitial oxygen elements can significantly strengthen titanium alloys and provide a large amount of strength contribution to titanium alloys, but as the oxygen content increases, the ductility of titanium alloys will drop sharply. Therefore, by adjusting the process parameters, the titanium alloy can accommodate more oxygen, achieve higher oxygen solid solution strengthening, and at the same time the ductility of the material will not be lost too much, ensuring that the oxygen content in the titanium alloy powder is increased, and the introduction of oxygen does not produce FCC phase, so that the material has no difference in mechanical properties at different build heights, and the mechanical properties of the alloy will not drop significantly, thereby achieving the preparation of high-strength and tough titanium alloys at a lower cost.

[0027] 2. Different laser power (P) and scanning speed (V) as well as spacing (h) and layer thickness (d) will jointly affect VED (volume energy density), VED = P / (V×h×d). The volume energy density has a greater effect on elongation, but has little effect on tensile strength. The reduction of volume energy density is conducive to the improvement of plasticity, which is mainly due to the refinement of α / α′ martensite and the reduction of nano-β phase, which leads to the enhancement of deformation coordination ability. However, when the volume energy density reaches a certain value, further reduction will not increase the elongation of the material (that is, its strengthening effect has a threshold). Higher volume energy density leads to local overheating or overburning of the molten pool, and liquid metal splashing may occur. Large-sized metal balls may have formed on the molding surface, resulting in discontinuity of the next powder layer and poor powder spreading effect. The scanning speed controls the time the laser stays on the powder surface. If the time is too long or too short, the powder will be over-melted or under-melted, which will cause some defects in the sample, thereby reducing the mechanical properties of the sample. Therefore, it is necessary to select appropriate process parameters to prepare samples with excellent mechanical properties.

[0028] 3. The average size of α grains decreases with increasing oxygen content, which can be attributed to the tendency of oxygen to segregate at grain boundaries and dislocations, and hinder dislocation slip / creep and grain boundary migration. Oxygen atoms prefer to occupy the octahedral gaps of the α-Ti lattice, resulting in the expansion of the lattice. The increase in oxygen content will cause the lattice parameters of the α phase in the alloy to change, the hardness to increase, thereby improving the strength of the material, but at the same time reducing the plasticity and impact toughness of the material. Reducing the oxygen content can significantly improve the crack propagation resistance and impact energy of the material, which is mainly due to the fact that at low oxygen content, the dislocation activation and subgrain boundary formation inside the alloy help to release internal stress and improve the plastic deformation coordination of the two phases. Additive manufacturing technology can prepare ultrafine grains, which makes it possible to accommodate more oxygen solid solution. When the oxygen content is 0.3%, the material can still maintain excellent mechanical properties through the process parameters of the present invention, but when the oxygen content reaches 0.5%, the elongation drops sharply.

[0029] 4. The present invention realizes a high-strength and plastic oxygen-containing titanium alloy with uniform performance and nano-twins as a strengthening mechanism through uniform distribution of TiO2 and specific process parameters. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 In the figure, (a) and (b) are powder morphology images of the titanium alloy prepared in Example 1 of the present invention, wherein (b) is an enlarged view of (a).

[0031] Figure 2 It is the three-dimensional digital model adopted by the present invention.

[0032] Figure 3It is a schematic diagram of the titanium alloy printed part of the present invention.

[0033] Figure 4 This is the microscopic morphology of the titanium alloy of sample No. 8 prepared in Example 8 of the present invention. DETAILED DESCRIPTION

[0034] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0036] The purity of the titanium dioxide powder used in the present invention is 99%. The titanium alloy powder and the TiO2 powder are mixed in an argon-filled glove box (the oxygen content inside the glove box is less than 0.1%) to ensure that the content of the O element in the mixed powder is x=0.1wt.%, 0.3wt.%, 0.5wt.%, and the mixing formula is:

[0037]

[0038] Example 1

[0039] A method for preparing a titanium alloy based on additive manufacturing technology comprises the following steps:

[0040] (1) Select TC4 powder that meets the requirements and perform drying treatment to remove moisture from the powder to ensure the quality of the powder and the printing effect, and fill the powder into a powder bin. Calculated by mass percentage, the composition of the TC4 powder is: Al: 6.27%, V: 3.97%, C: 0.0111%, Fe: 0.032%, O: 0.0833%, N: 0.0148, Ti: 0.0148, Ti balance, totaling 100%.

[0041] (2) The TC4 powder and TiO2 powder in step (1) are mixed in a V-type mixer for 12 hours, wherein the mass percentage of oxygen in the mixed powder is 0.1%.

[0042] (3) Figure 2The three-dimensional digital model shown in the figure and the relevant process parameters for printing are imported into the BLT-S210 laser printing device, and the printer is set to print. The preheating parameters are set, and the preheating temperature is 200°C. According to the printing strategy, the printing path is set to unidirectional scanning, the printing layer thickness is 60μm, and the printing parameters are: laser power: 175W, scanning speed: 840mm / s, scanning spacing: 80μm, volume energy density: 43J / mm 3 , and obtain titanium alloy formed parts based on additive manufacturing technology.

[0043] Example 2

[0044] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 150 W, scanning speed: 600 mm / s, scanning spacing: 80 μm, volume energy density: 52 J / mm 3 .

[0045] Example 3

[0046] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 175 W, scanning speed: 600 mm / s, scanning spacing: 80 μm, volume energy density: 61 J / mm 3 .

[0047] Example 4

[0048] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 200 W, scanning speed: 600 mm / s, scanning spacing: 80 μm, volume energy density: 70 J / mm 3 .

[0049] Example 5

[0050] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 150 W, scanning speed: 720 mm / s, scanning spacing: 80 μm, volume energy density: 43 J / mm 3 .

[0051] Example 6

[0052] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 175 W, scanning speed: 720 mm / s, scanning spacing: 80 μm, volume energy density: 51 J / mm 3 .

[0053] Example 7

[0054] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 200 W, scanning speed: 720 mm / s, scanning spacing: 80 μm, volume energy density: 58 J / mm 3 .

[0055] Example 8

[0056] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 150 W, scanning speed: 840 mm / s, scanning spacing: 80 μm, volume energy density: 37 J / mm 3 .

[0057] Example 9

[0058] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 200 W, scanning speed: 840 mm / s, scanning spacing: 80 μm, volume energy density: 50 J / mm 3 .

[0059] Example 10

[0060] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 375 W, scanning speed: 1500 mm / s, scanning spacing: 80 μm, volume energy density: 52 J / mm 3 .

[0061] Embodiment 11

[0062] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 150 W, scanning speed: 430 mm / s, scanning spacing: 100 μm, volume energy density: 58 J / mm 3 .

[0063] Example 12

[0064] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 175 W, scanning speed: 430 mm / s, scanning spacing: 100 μm, volume energy density: 68 J / mm 3 .

[0065] Embodiment 13

[0066] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 200 W, scanning speed: 430 mm / s, scanning spacing: 100 μm, volume energy density: 78 J / mm 3 .

[0067] Embodiment 14

[0068] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 150 W, scanning speed: 576 mm / s, scanning spacing: 100 μm, volume energy density: 43 J / mm 3 .

[0069] Embodiment 15

[0070] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 175 W, scanning speed: 576 mm / s, scanning spacing: 100 μm, volume energy density: 51 J / mm 3 .

[0071] Example 16

[0072] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 200 W, scanning speed: 576 mm / s, scanning spacing: 100 μm, volume energy density: 58 J / mm 3 .

[0073] Embodiment 17

[0074] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 150 W, scanning speed: 722 mm / s, scanning spacing: 100 μm, volume energy density: 35 J / mm 3 .

[0075] Embodiment 18

[0076] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 175 W, scanning speed: 722 mm / s, scanning spacing: 100 μm, volume energy density: 40 J / mm 3 .

[0077] Embodiment 19

[0078] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 200 W, scanning speed: 722 mm / s, scanning spacing: 100 μm, volume energy density: 46 J / mm 3 .

[0079] Embodiment 20

[0080] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 375 W, scanning speed: 1500 mm / s, scanning spacing: 100 μm, volume energy density: 42 J / mm 3 .

[0081] Embodiment 21

[0082] The preparation method is the same as that of Example 1, except that the printing parameters are: laser power: 375 W, scanning speed: 1500 mm / s, scanning spacing: 120 μm, volume energy density: 51 J / mm 3 .

[0083] Embodiment 22

[0084] A method for preparing a titanium alloy based on additive manufacturing technology comprises the following steps:

[0085] (1) Select TC4 powder that meets the requirements and perform drying treatment to remove moisture from the powder to ensure the quality of the powder and the printing effect, and fill the powder into a powder bin. Calculated by mass percentage, the composition of the TC4 powder is: Al: 6.27%, V: 3.97%, C: 0.0111%, Fe: 0.032%, O: 0.0833%, N: 0.0148, Ti: 0.0148, Ti balance, totaling 100%.

[0086] (2) The TC4 powder and TiO2 powder in step (1) are mixed in a V-type mixer for 12 hours, wherein the mass percentage of oxygen in the mixed powder is 0.3%.

[0087] (3) Figure 2 The three-dimensional digital model shown in the figure and the relevant process parameters for printing are imported into the BLT-S210 laser printing device, and the printer is set to print. The preheating parameters are set, and the preheating temperature is 200°C. According to the printing strategy, the printing path is set to unidirectional scanning, the printing layer thickness is 60μm, and the printing parameters are: laser power: 175W, scanning speed: 840mm / s, scanning spacing: 80μm, volume energy density: 43J / mm 3 , and obtain titanium alloy formed parts based on additive manufacturing technology.

[0088] Embodiment 23

[0089] The preparation method is the same as that of Example 22, except that the printing parameters are: laser power: 150 W, scanning speed: 720 mm / s, scanning spacing: 80 μm, volume energy density: 43 J / mm 3 .

[0090] Embodiment 24

[0091] A method for preparing a titanium alloy based on additive manufacturing technology comprises the following steps:

[0092] (1) Select TC4 powder that meets the requirements and perform drying treatment to remove moisture from the powder to ensure the quality of the powder and the printing effect, and fill the powder into a powder bin. Calculated by mass percentage, the composition of the TC4 powder is: Al: 6.27%, V: 3.97%, C: 0.0111%, Fe: 0.032%, O: 0.0833%, N: 0.0148, Ti: 0.0148, Ti balance, totaling 100%.

[0093] (2) The TC4 powder and TiO2 powder in step (1) are mixed in a V-type mixer for 12 hours, wherein the mass percentage of oxygen in the mixed powder is 0.5%.

[0094] (3) Figure 2 The three-dimensional digital model shown in the figure and the relevant process parameters for printing are imported into the BLT-S210 laser printing device, and the printer is set to print. The preheating parameters are set, and the preheating temperature is 200°C. According to the printing strategy, the printing path is set to unidirectional scanning, the printing layer thickness is 60μm, and the printing parameters are: laser power: 175W, scanning speed: 840mm / s, scanning spacing: 80μm, volume energy density: 43J / mm 3 , and obtain titanium alloy formed parts based on additive manufacturing technology.

[0095] Embodiment 25

[0096] The preparation method is the same as that of Example 24, except that the printing parameters are: laser power: 150 W, scanning speed: 720 mm / s, scanning spacing: 80 μm, volume energy density: 43 J / mm 3 .

[0097] Results Analysis

[0098] Figure 1 In the figure, (a) and (b) are powder morphology images of the titanium alloy prepared in Example 1 of the present invention, wherein (b) is an enlarged view of (a). From the morphology image, it can be clearly seen that TiO2 has no agglomeration and unevenness, and from (b) it can be seen that TiO2 is evenly distributed on the powder particles of TC4. Table 1 is a list of printing parameters of Examples 1 to 21 of the present invention.

[0099] Table 1 Printing parameters in Examples 1 to 21

[0100]

[0101]

[0102] Table 2 Mechanical properties of TC4-0.1O (wt.%) specimens with different printing parameters

[0103]

[0104]

[0105] The schematic diagram of the formed part prepared in Example 1 is as follows Figure 3 As shown, the formed part prepared by the present invention is subjected to wire cutting, and three tensile samples are cut from top to bottom and polished to 80 mesh, 220 mesh, 400 mesh, 800 mesh, 1000 mesh, and 1500 mesh. After polishing, they are stretched. The tensile properties of 21 groups of tensile samples are shown in Table 2. It can be seen that the best mechanical property is sample No. 8. The tensile test of sample No. 8 at the top, middle and bottom positions is carried out. Its mechanical properties are shown in Table 3. It is found that the mechanical properties of the titanium alloy prepared by the method of the present invention are no different at different building heights. The process parameters determined by the first printing can further increase the oxygen content, and the mass fraction of the oxygen content is changed to 0.3% and 0.5%, and the printing is continued. When the oxygen content is 0.3%, its mechanical properties are shown in Table 4, and when the oxygen content is 0.5%, its mechanical properties are shown in Table 5. The average size of the α grains decreases with the increase of the oxygen content, which can be attributed to the tendency of oxygen to segregate at grain boundaries and dislocations, and hinder dislocation slip / creep and grain boundary migration. Oxygen atoms prefer to occupy the octahedral gaps of the α-Ti lattice, resulting in the expansion of the lattice. The increase in oxygen content will cause the lattice parameters of the α phase in the alloy to change, the hardness to increase, thereby improving the strength of the material, but at the same time reducing the plasticity and impact toughness of the material. Reducing the oxygen content can significantly improve the crack propagation resistance and impact energy of the material. This is mainly because at low oxygen content, the dislocation activation and subgrain boundary formation inside the alloy help release internal stress and improve the plastic deformation coordination of the two phases. Additive manufacturing can prepare ultrafine grains, which makes it possible to accommodate more oxygen solid solution. When the oxygen content is 0.3%, the material can still maintain excellent mechanical properties, but when the oxygen content reaches 0.5%, the elongation drops sharply.

[0106] Table 38 Mechanical properties of top and midsole

[0107] Sample Yield strength / MPa Tensile strength / MPa Elongation / % top 950 1090 11.5 middle 950 1090 11.5 end 950 1090 11.5

[0108] Table 4 Mechanical properties of specimens with oxygen content of 0.3%

[0109] Sample Yield strength / MPa Tensile strength / MPa Elongation / % 1(8) 1100 1300 10.0 2(5) 1100 1200 8.0

[0110] Table 5 Mechanical properties of specimens with oxygen content of 0.5%

[0111] Sample Yield strength / MPa Tensile strength / MPa Elongation / % 1(8) 1300 1500 6.0 2(5) 1300 1400 4.0

[0112] Figure 4From the micromorphology of the titanium alloy of sample No. 8 prepared in Example 8 of the present invention, it can be seen that its microstructure is an HCP twin band. Since the formation of the FCC phase is the result of the combined effects of high temperature, thermal stress, rapid cooling and non-equilibrium phase transformation, the controllable formation of FCC can be achieved by regulating the alloy composition and process parameters. This patent optimizes the process parameters through additive manufacturing technology, realizes the effective regulation of residual stress in the titanium alloy, inhibits the formation of the FCC phase, and promotes the generation of HCP twin bands. The evolution of this microstructure transforms the strengthening mechanism of the titanium alloy into nano-twin strengthening, and ultimately achieves the synergistic improvement of the homogenization and toughness of the material properties.

[0113] In summary, the present invention is based on the prior art that usually sacrifices plasticity to improve the strength of titanium alloys. By adding TiO2 to the titanium alloy powder, the mass percentage of oxygen in the mixed powder is 0.1-0.5, and the printing parameters of the additive manufacturing technology are adjusted as follows: laser power: 150W-375W, scanning speed: 430mm / s-1500mm / s, scanning spacing: 80μm-120μm, volume energy density: 35J / mm 3 ~78J / mm 3 The present invention achieves more oxygen solid solution through additive manufacturing technology and adjustment of process parameters. This is because interstitial oxygen elements can significantly strengthen titanium alloys and provide a large amount of strength contribution to titanium alloys. However, as the oxygen content increases, the ductility of titanium alloys decreases sharply. Therefore, by adjusting the process parameters, the titanium alloy can accommodate more oxygen, achieving higher oxygen solid solution strengthening while the ductility of the material will not be lost too much, ensuring that the oxygen content in the titanium alloy powder is increased and the mechanical properties of the alloy will not decrease significantly, thereby achieving the preparation of high-strength and tough titanium alloys at a lower cost.

[0114] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0115] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the protection scope of the present invention and its equivalent technology, the present invention is also intended to include these changes and variations.

Claims

1. A method for preparing a nano-twinned oxygen-containing titanium alloy based on additive manufacturing technology, characterized in that: The following steps are involved: Mixing titanium alloy powder and TiO2 powder under vacuum conditions to obtain mixed powder, wherein the mass percentage of oxygen in the mixed powder is 0.1% to 0.5%; Laser printing the mixed powder to obtain a titanium alloy based on additive manufacturing technology; The printing parameters are: laser power: 150W~375W, scanning speed: 430mm / s~1500mm / s, scanning spacing: 80μm~120μm, volume energy density: 35J / mm 3 ~78J / mm 3 .

2. The method for preparing nano-twinned oxygen-containing titanium alloy based on additive manufacturing technology according to claim 1, characterized in that: Printing parameters: laser power: 175W, scanning speed: 720mm / s~840mm / s, scanning spacing: 80μm, volume energy density: 43J / mm 3 ~51J / mm 3 .

3. The method for preparing nano-twinned oxygen-containing titanium alloy based on additive manufacturing technology according to claim 1, characterized in that: The particle size of the titanium alloy powder is 15 μm to 53 μm, and the particle size of the TiO2 powder is 200 nm to 300 nm.

4. The method for preparing nano-twinned oxygen-containing titanium alloy based on additive manufacturing technology according to claim 1, characterized in that: The printing layer thickness is 55μm~65μm.

5. The method for preparing nano-twinned oxygen-containing titanium alloy based on additive manufacturing technology according to claim 1, characterized in that: The printing path is unidirectional scanning.

6. The method for preparing nano-twinned oxygen-containing titanium alloy based on additive manufacturing technology according to claim 1, characterized in that: The titanium alloy powder comprises, by mass percentage, Al: 5.5%-7%, V: 3.5%-5%, C: <0.1%, Fe: <0.1%, O: <0.1%, N: <0.1%, and the remainder Ti, which is 100% in total.

7. The method for preparing nano-twinned oxygen-containing titanium alloy based on additive manufacturing technology according to claim 1, characterized in that: The substrate is preheated before printing, and the preheating temperature is 190℃~210℃.

8. A nano-twinned oxygen-containing titanium alloy prepared by the preparation method according to any one of claims 1 to 7 based on additive manufacturing technology.

9. The nano-twinned oxygen-containing titanium alloy based on additive manufacturing technology according to claim 8, characterized in that: The mass percentage of oxygen in the titanium alloy is 0.1% to 0.5%, the yield strength is 810MPa to 1300MPa, the tensile strength is 905MPa to 1500MPa, and the elongation is 4.0% to 11.5%.

10. The nano-twinned oxygen-containing titanium alloy based on additive manufacturing technology according to claim 8, characterized in that: The microstructure of titanium alloy is nano twins.

Citation Information

Cited By

  • Electron beam additive manufacturing method of oxygen-enriched titanium alloy

    CN121199121A

  • Method for constructing titanium alloy heterostructure in situ by mixing alpha-rich and beta-rich powders

    CN122769463A